PENGARUH PROMOSI KESEHATAN TENTANG PENCEGAHAN DAN PENGENDALIAN DBD TERHADAP PENGETAHUAN KADER JUMANTIK DI KELURAHAN CAKUNG BARAT JAKARTA TIMUR TAHUN 2022 - Desi Wulandari (2022)
Jumantik cadres as volunteers and health promoters in the community are very much needed. To support this role, good knowledge is needed in order to provide information about the prevention and control of DHF and can motivate the community to take preventive action against the spread of DHF. This study aims to determine the effect of health promotion on the knowledge of cadres. This research is quantitative with a pre-experimental study design with a one group pretest and posttest design approach, using a total sampling technique. The number of research samples was 83 jumantik cadres. Data collection was carried out using an instrument in the form of a research questionnaire. The analysis was carried out using the Wilcoxon test. The results of this study indicate that before being given health promotion on prevention and control of DHF the average score of knowledge was 58,28 after being given health promotion there was an increase in the average score to 77,51. The resulting p-value is 0,000 (p < 0,05), so it can be concluded that there is a difference in the level of knowledge and there is an effect of health promotion on the knowledge of jumantik cadres in Cakung Barat Village about the prevention and control of DHF. With the health promotion provided, it is hoped that cadres can provide socialization related to the prevention and control of DHF to the community, with increased knowledge, it is expected to be able to influence people's attitudes and behavior to maintain cleanliness in order to reduce the spread of DHF in the local environment.